OPTIMALISASI PRODUKSI GULA LEMPENG DAN GULA AIR MENGGUNAKAN PROGRAM LINEAR METODE SIMPLEKS - Aso, Maria Lidvina; Roni, Epifani; Bhiju, Vinsensia; Tahun, Herodiana; Adoe, Vera Selviana (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
This study aims to optimize the production of flat sugar and water sugar in MSMEs owned by Mrs. Yane Pandie in Oebelo Dalam using the linear programming (LP) method and the simplex method. Data collected through interviews, observations, and literature studies were processed using the POM-QM application to determine the optimal production volume, maximize profits, and minimize production costs. The main constraints faced are the limited raw materials such as sap and firewood and the need for packaging. The optimization results show that to achieve maximum profit, the company must produce flat sugar 2 times per cycle without producing water sugar. Constraint analysis shows that increasing the availability of sap can increase profitability. This method allows producers to plan resource allocation efficiently, respond effectively to market demand, and increase competitiveness in the industry